The driving factors of china's public‐private partnership projects in Metropolitian transportation systems: Public sector's viewpoint - Yuan, Jing-Feng; J. Skibniewski, Mirosław; Li, Qiming; Shan, Jin (Journal of Civil Engineering and Management, 2010)
In recent years, China needs far more financing for transportation infrastructure than can be provided by the government alone. Meanwhile the capacity of the Chinese government to provide public services on its own in an effective and efficient way is being questioned and reassessed at various levels. Accordingly, the involvement of private investors in the development of Metropolitan Transportation Systems (MTS) has been promoted by the Chinese public sector by means of adopting the Public Private Partnership (PPP) model. However, China's dynamic and complex political, financial, legal and regulatory environment makes the private sector adjust to accommodate the existing regime by way of understanding the driving factors in PPP applications for improving the chances of project success. This paper presents two case studies in China's MTS. Based on a case study and comprehensive literature review, 15 driving factors associated with PPP projects from the perspective of the Chinese public sector have been identified. A structured questionnaire survey targeting the public sector has been conducted to seek, analyze and integrate its perception of the driving factors. Through statistical analysis of the relative significance of each of these driving factors, the writers determined five common major dimensions of the Chinese public sector's purpose in developing PPP schemes, and the key factors that quantify each purpose. The establishment of the measures for these objectives and the key factors that quantify each of these purposes will likely be useful in encouraging private participation in infrastructure management and directing/concentrating efforts of the private sector to deliver quality public services under mutually beneficial long‐term contractual arrangements.First Published Online: 15 Oct 2010